Advanced load blinding of distance protection relays based on physical grid limitations - Schindler, Josef; Jäger, Johann (IEEE Power and Energy Society General Meeting, 2016)
The encroachment of the measured load impedance into the outer tripping zone was one of the main problems of distance protection relays since their application. Highly loaded transmission lines intensified this issue and caused cascading failures worldwide during the last decades. Restricted zone reach settings or load blinders in the R-X-impedance plane were the common countermeasures until now. These measures were performed from the point of view of the relay. The objective of this paper was to propose an approach from the point of view of the grid and its physical loading limitations regarding bus voltage und line current. This approach helped to find out the load blinder with the best possible degree of dependability and security. A comprehensive analytical description of the physical loading and stability limits of the grid was used to identify the steady state operation limits in the impedance plane. Analytical calculation results demonstrated that the proposed approach is capable of achieving an optimized shape of load blinder increasing the dependability and security compared to blinders used in distance protection relays today.
Created from Fastlane, Scopus look-up
Keywords: Distance protection; Impedance plane; Load blinder; Load encroachment; Physical grid limitations